Variable clinical severity in TANGO2 deficiency: Case series and literature review. Issue 2 (19th October 2021) - Schymick, Jennifer; Leahy, Peter; Cowan, Tina; Ruzhnikov, Maura R. Z.; Gates, Ryan; Fernandez, Liliana; Pramanik, Gopal; ,; Yarlagadda, Vamsi; Wheeler, Matthew; Bernstein, Jonathan A.; Enns, Gregory M.; et al.
Abstract: Biallelic pathogenic variants in the TANGO2 (transport and Golgi organization 2 homolog) gene have been identified as causing a rare metabolic disorder characterized by susceptibility to recurrent rhabdomyolysis, lactic acidosis, encephalopathy, and life‐threatening tachyarrhythmias. Recently published reports suggest variable clinical severity and phenotypes. This study details five new patients from two families with biallelic pathogenic variants in the TANGO2 gene identified by whole exome sequencing and includes the largest number of affected individuals from a single family reported to date. We document significant intrafamilial variability and highlight that milder phenotypes may be underrecognized. We present biochemical and clinical data to help highlight the features that aid in consideration of this condition in the differential with disorders of fatty acid oxidation. We also present a comprehensive literature review summarizing the molecular, clinical, and biochemical findings for 92 individuals across 13 publications. Of the 27 pathogenic variants reported to date, the recurrent exons 3–9 deletion represents the most common variant seen in 42% of individuals with TANGO2 deficiency. Common clinical features seen in >70% of all individuals include acute metabolic crisis, rhabdomyolysis, neurologic abnormalities, developmental delay, and intellectual disability. Findings such as elevated creatine kinase, hypothyroidism, ketotic hypoglycemia, QT prolongation, or abnormalities of long‐chain acylcarnitines and urine dicarboxylic acids should raise clinical suspicion for this life‐threatening condition.